Law Enforcement Against Perpetrators of Violence Sexual Against Children in the Decision Number 100/Pid.Sus/2025/PN.Sgr - Nabila Budiman; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Journal of Judicial Review, 2026)
Sexual violence against children constitutes a serious violation of human rights, with far-reaching consequences in physical, psychological, social, and moral dimensions. In cases involving sexual violence against children, law enforcement should ideally not only emphasize the punishment of perpetrators but also prioritize victim recovery and preventive measures to ensure that similar crimes do not recur.  The findings of this study indicate that, first, law enforcement in Decision Number 100/Pid.Sus/2025/PN.Sgr has not yet demonstrated concrete measures to ensure the psychological recovery of the victim. In essence, victim recovery is an inseparable element of substantive justice. From the perspective of progressive law, judges should not merely act as the “mouthpiece of the law,” but should also serve as active agents in realizing social justice within society. Although the decision reflects the principle of legal certainty, the dimensions of substantive justice and humanitarian values still need to be strengthened so that law enforcement against perpetrators of sexual violence against children can genuinely side with the victims. Second, Law Number 35 of 2014 explicitly mandates the state to protect children from all forms of violence, exploitation, and discrimination. Within this framework, the principle of the best interests of the child must serve as the primary consideration in every legal policy and court decision. However, in the Singaraja District Court Decision, this principle has not been fully implemented, as the judgment does not include an order for the victim’s psychological recovery. The absence of provisions concerning victim rehabilitation and the restoration of the victim’s rights indicates that the aspect of child protection has not been optimally accommodated. Therefore, strengthening the implementation of a restorative justice approach within the national legal system is necessary to ensure that substantive justice can be realized for child victims of sexual violence.